THE EFFECTIVENESS OF THE SCIENCE TECHNOLOGY COMMUNITY APPROACH (STM) ON STUDENT LEARNING OUTCOMES ON ECOSYSTEM CONCEPTS AT SMA NEGERI 1 SEUNAGAN, NAGAN RAYA REGENCY - Hasanah, Mauizah; Hanum, Ulia (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2023)
Science and technology are two things that cannot be separated from human life. Almost all aspects of human life today have been touched by technological products which are the application of scientific concepts, STM is a learning model that can invite students to find new ideas or ideas that exist in society so that they can make students active and motivated. This study aims to determine the effectiveness of the science and technology community (STM) approach to student learning outcomes on the concept of ecosystems. The method used in this study is a quantitative descriptive experimental method. The results obtained are the tcount value of 5.80, with a significant level of α = 0.05 and dk = 68, the value of t(1- α) = t(0.95)(68) = is 1.67. The conclusion of this study shows that students who are taught using the STM approach have better learning outcomes than those who do not use the STM approach to the ecosystem concept at SMA Negeri 1 Seunagan, Nagan Raya Regency.